(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
This study examines the relationship between board size and firm performance, a critical topic in corporate governance research. While larger boards are often associated with enhanced diversity and broader expertise, they may also face challenges in coordination and decision-making. Conversely, smaller boards can be more agile and cohesive but may lack diverse perspectives. Based on 5215 companies over the period of 2005 to 2022 this research revealed a increasing returns (Tobin’s Q) upto certain level of board size which eventually converted to diminishing return beyond certain board size. The findings emphasized the importance of optimal board composition in maximizing firm value. These results provide insights for policymakers, shareholders, and corporate managers in designing governance structures that align with firm goals and industry characteristics.